Assessment of sheep production system in Burie District, north western Ethiopia - Abebe, Yenenesh; Melaku, S.; Tegegne, Azage; Tegegne, F. (2013)
The study was conducted in Burie District to assess the sheep production system and to identify and prioritize the sheep production constraints. Informal and formal surveys were conducted in four selected kebeles of Burie District, namely, Woheni Durebetie, Woyenema Ambaye, Denbun and Boko Tabo. The farmers interviewed in the informal survey were selected purposively and for the formal survey, by systematic random sampling method. Farmers rear sheep for two main purposes, for cash income and home slaughter on festivals. On average, one household had 3.7±2.46 heads of sheep (n = 127). Washera and Horro sheep breeds were found in the area. There were more Washera sheep (98%) in Woheni Durebetie Kebele and more Horro sheep (92%) in Boko Tabo Kebele. The main feed resources for sheep were natural pasture and stubble grazing. Most farmers supplement common salt and Atella (a local beer (Tela) residue) to their sheep. Feed shortage occurs both during the dry and rainy seasons in the highland kebeles. There was a deficit of 0.7 ton DM feed per household per year in the highland kebeles. The sheep production system is subsistence-oriented. Sheep diseases, lack of adequate veterinary service and feed and nutrient shortage were the main sheep production constraints in the area in that order of importance. To improve sheep production in Burie District, these constraints should be given more emphasis in research and development activities that are going to be undertaken in the study area.